Induction of haploids in wheat using Wheat x Maize system of chromosome elimination - Gupta, Vikas; Kumar, Satish; Singroha, Garima; Mishra, Chandra Nath; Kumar, Raj; Tiwari, Vinod (Journal of Cereal Research, 2016)
The present study was undertaken with the objective to standardize the wheat x maize protocol for haploid production using different crosses (F1s) and commercial wheat varieties. In case of varieties, caryopsis formation frequency ranged between 25.9 to 51.4 %, embryo formation frequency ranged between 4.6 to 22.4 % and plant regeneration frequency ranged between 6.4 to 63.6 %. The caryopsis formation frequency among F1’s ranged between 21.4 to 60.5%, embryo formation frequency ranged between 1.3 to 21.2 % and plant regeneration frequency ranged between 9.8 to 44.4 %. A total of 100 haploid plantlets were regenerated and transferred to pots containing pot mixture for hardening and acclimatization. The surviving plants were given colchicine treatment of 0.1 % for chromosome doubling. For efficient utilization of wheat x maize protocol factors like embryo formation, induction of haploid embryo germination by cold treatment and chromosome doubling have been identified for further studies.